Indications and techniques for submucosal dissection in duodenal stump closure - Ardao, Hector A.; Balboa, Oscar; Mayol, Ricardo (Cirugía del Uruguay, 1977)
A valuable procedure for obtaining sufficient wall for correct closurc of duodenal stump, is submucose dissection of duodenum. It supports gastrectomy in treatment of duodenal ulcer. A detailed description of anato¡nical .basis and surgical technique is contained in this paper.